Reintroduce Thalidomide? (A) - Diermeier, Daniel, (SAGE Knowledge. Cases., 2006)
The case charts the history of the drug thalidomide from its dark beginnings causing child birth defects to the discovery that the drug could be used in the treatment of leprosy, certain cancers and HIV/Aids. The student is invited to consider how the FDA responded and approved the use of thalidomide for the treatment of these diseases.